HOTAIR contributes to cell proliferation and metastasis of cervical cancer via targetting miR-23b/MAPK1 axis. Issue 1 (8th February 2018) - Li, Qin; Feng, Yanhong; Chao, Xu; Shi, Shuai; Liang, Man; Qiao, Yumei; Wang, Bin; Wang, Pin; Zhu, Zhenning
Abstract : The long non-coding RNA (lncRNA) HOX transcript antisense RNA (HOTAIR) has been found to be overexpressed in many human malignancies and involved in tumor progression and metastasis. Although the downstream target through which HOTAIR modulates tumor metastasis is not well-known, evidence suggests that miR-23b might be involved in this event. In the present study, the expressions of HOTAIR and miR-23b were detected by real-time PCR in 33 paired cervical cancer tissue samples and cervical cell lines. The effects of HOTAIR on the expressions of miR-23b and mitogen-activated protein kinase 1 (MAPK1) were studied by overexpression and RNAi approaches. We found that HOTAIR expression was significantly increased in cervical cancer cells and tissues. In contrast, the expression of miR-23b was obviously decreased. We further demonstrated that HOTAIR knockdown promoted apoptosis and inhibited cell proliferation and invasion in vitro and in vivo . Moreover, our data indicated that HOTAIR may competitively bind miR-23b and modulate the expression of MAPK1 indirectly in cervical cancer cells. Taken together, our study has identified a novel pathway through which HOTAIR exerts its oncogenic role, and provided a molecular basis for potential applications of HOTAIR in the prognosis and treatment of cervical cancer.